Hubungan Antara Literasi Digital dengan Kemampuan Berpikir Kritis Generasi Z - Nurul Pauziah; Tia Muthiah (Bandung Conference Series: Communication Management, 2023)
Abstract. Currently, the advancement of information technology is so rapid which has implications for the ease of humans in interacting and transacting. The convenience obtained for human life is to launch daily activities / activities, such as work, school, and college. Through various information technology devices, humans can obtain all kinds of information that can be accessed easily and cheaply through social media networking sites. The most popular social media networking site by the public is YouTube, where Indonesian people are ranked 3rd YouTube users in the world. This study is entitled "The Relationship Between Digital Literacy and Critical Thinking Skills on YouTube Media Networking Sites" the purpose of this study is to determine the relationship between digital literacy and critical thinking skills of Generation Z YouTube media. The method used is a quantitative method with a correlational study approach with the help of the SPSS application which aims to find out whether there is a relationship between digital literacy in technical, cognitive and social-emotional dimensions with the critical thinking ability of generation z when they are operating YouTube social media. The respondents of the study were 100 people, the sample was set according to the slovin formula. Meanwhile, the data collection technique used in this study was through questionnaires. The results of this study showed that the technical dimension was positively related to low relationship strength, the cognitive dimension was positively related to moderate relationship strength, the social-emotional dimension was positively related to strong relationship strength. Abstrak. Saat ini kemajuan teknologi informasi demikian pesat yang berimplikasi pada kemudahan manusia dalam berinteraksi dan bertransaksi. Kemudahan yang diperoleh bagi kehidupan manusia adalah melancarkan kegiatan/aktivitas sehari-hari, seperti bekerja, sekolah, dan kuliah. Melalui berbagai perangkat teknologi informasi, manusia dapat memperoleh segala jenis informasi yang dapat diakses secara mudah dan murah melalui media sosial. media sosial yang paling banyak diminati oleh masyarakat adalah YouTube, dimana masyarakat Indonesia termasuk dalam peringkat ke 3 pengguna YouTube di dunia. Penelitian ini berjudul “Hubungan Antara Literasi Digital dengan Kemampuan Berpikir Kritis Generasi Z” tujuan dari penelitian ini untuk mengetahui hubungan antara literasi digital dengan kemampuan berpikir kritis Generasi Z media YouTube. Metode yang digunakan adalah metode kuantitatif dengan pendekatan studi korelasional dengan bantuan aplikasi SPSS yang bertujuan untuk mengetahui apakah terdapat hubungan antara literasi digital pada dimensi technical, cognitive dan social-emotional dengan kemampuan berpikir kritis Generasi Z pada saat mereka sedang mengoperasikan media sosial YouTube. Responden dari penelitian ini adalah 100 orang, sampel ditetapkan berdasarkan rumus slovin. Sementara itu teknik pengumpulan data yang digunakan dalam penelitian ini melalui kuesioner. Hasil penelitian ini menunjukkan bahwa dimensi technical berhubungan positif dengan kekuatan hubungan yang rendah, dimensi cognitive berhubungan positif dengan kekuatan hubungan yang sedang, dimensi social-emotional berhubungan positif dengan kekuatan hubungan yang kuat.